2022
DOI: 10.1111/nicc.12741
|View full text |Cite
|
Sign up to set email alerts
|

Effect of earplug/eye mask on sleep and delirium in intensive care patients

Abstract: Background: Environmental factors such as loud sounds and bright lights in intensive care units can cause sleep disorders and delirium.Aim: The present study aims to investigate the effects of the overnight use of earplugs and eye masks by intensive care patients on their sleep quality and the degree of delirium.Study Design: This randomized controlled experimental study was conducted on the patients admitted to a coronary intensive care unit. Methods:The patients in the experimental group used earplugs and ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…While fifty percent of the intervention group had good sleep quality compared to control group. Also, Akpinar R et al, (2022) (34) emphasized this result. As regard incidence of ICU acquired delirium, the present finding revealed a minority sample of the study group that had delirium compared with the control group.…”
Section: Discussionmentioning
confidence: 79%
“…While fifty percent of the intervention group had good sleep quality compared to control group. Also, Akpinar R et al, (2022) (34) emphasized this result. As regard incidence of ICU acquired delirium, the present finding revealed a minority sample of the study group that had delirium compared with the control group.…”
Section: Discussionmentioning
confidence: 79%
“…In studies, it is seen that the education levels are equal, along with other factors, between the intervention and control groups. 17,20,23,32,33 According to the results of the study, the high level of education of the intervention group and the lower incidence of delirium compared with the control group suggest that they use eye masks and earplugs per instructed and that the level of education may have an effect on the delirium.…”
Section: B Level Of Sedation and Level Of Consciousnessmentioning
confidence: 94%
“…34 In A randomized controlled study by Akpınar et al reported that while the use of earplugs and eye masks during the night decreased the perceived noise level of the patients, it also increased their sleep quality and reduced the degree of delirium. 32 Additionally, a recent metaanalysis highlighted that the use of earplugs and eye masks was associated with a significant reduction in the incidence of delirium. 21 Systematic review study by Polat et al earplugs and eye masks were found to have potential positive effects on sleep quality and delirium incidence.…”
Section: B Level Of Sedation and Level Of Consciousnessmentioning
confidence: 99%
“…As patients were randomized, trial registration is still essential, and the authors have done this. The third RCT by Akpinar 5 randomized patients in a coronary care unit in Turkey to receive either earplugs and eye masks or usual care (neither) to determine whether they impacted the patients' sleep quality and the occurrence of delirium. The last trial in this issue, also conducted in Turkey, investigated whether abdominal massage influenced bowel evacuation in neurosurgical adult patients 6 .…”
mentioning
confidence: 99%
“…The four trials in this issue, 3–6 include a pilot RCT 2 . In the first trial by Siebert et al 3 paediatric critical care staff in a Swiss tertiary hospital were randomized to either receive a face to Face or a blended learning approach to the use of a manual defibrillator.…”
mentioning
confidence: 99%